Studies on the constituents of a Brazilian folk infusion. Isolation and structure elucidation of new triterpene saponins from Ilex amara leaves - de Andrade, FDP; Piacente, S.; Pizza, C.; Vilegas, Wagner [UNESP] (Amer Chemical Soc, 2002)
The isolation of three new triterpene saponins 3beta-O-beta-D-glucopyranosyl-(1-->3)-alpha-L-2-O-acetylara-binopyranosylolean-12-en-28-oic acid 28-O-beta-D-glucopyranosyl ester (2), 3beta-O-beta-D-glucopyranosyl-(1-->2)-alpha-L-O-arabinopyranosylurs-12-en-28-oic acid (3), and 3beta-O-beta-D-glucopyranosyl-(1-->2)-beta-D-O-galactopyranosylurs-12-en-28-oic acid (4) together with five known saponins and one flavonoid glycoside from the aqueous infusion of flex amara (Vellozo) Loes. leaves is reported. All structures were elucidated by spectroscopic methods, including the concerted application of one-dimensional (H-1, TOCSY, C-13, and C-13 DEPT NMR) and two-dimensional NMR techniques (DQF-COSY, HSQC, and HMBC).
Keywords: Ilex amara (Vellozo) Loes.; Aquifollaceae; mate; Infusion; triterpene saponins; 1D and 2D NMR